2001
DOI: 10.1021/ja002724g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nucleation for CVD Diamond Growth

Abstract: A new nucleation method to form diamond by chemically pretreating silicon (111) surfaces is reported. The nucleation consists of binding covalently 2,2-divinyladamantane molecules on the silicon substrate. Then low-pressure diamond growth was performed for 2 h via microwave plasma CVD in a tubular deposition system. The resulting diamond layers presented a good cristallinity and the Raman spectra showed a single very sharp peak at 1331 cm(-1), indicating high-quality diamonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…It is interesting that nucleation of diamond from cage compounds of carbon and hydrogen atoms was also proposed for diamond growth by CVD technique from mixture of methane with hydrogen . Later the successful growth of CVD diamond crystals from adamantane seeds has been widely reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that nucleation of diamond from cage compounds of carbon and hydrogen atoms was also proposed for diamond growth by CVD technique from mixture of methane with hydrogen . Later the successful growth of CVD diamond crystals from adamantane seeds has been widely reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Such covalent attachment then alleviates issues with the low sublimation point of adamantane and increases the likelihood of the molecules acting as nucleation sites upon being subjected to plasma conditions. 22 At the end of exposure, the samples were twice alternately rinsed in ethanol and deionized water for 30 s to remove the excess DVA. Subsequent sonication for 5 min in a portion of dichloromethane then removed ungrafted DVA and residual traces of solvents.…”
Section: Methodsmentioning
confidence: 99%
“…This led Leroy et al 21 to design adamantane based 2,2-divinyladamantane (DVA) for chemical nucleation of diamond consisting of the smallest diamondoid, adamantane (C 10 H 16 ), with two vinyl groups to facilitate covalent attachment to the silicon surface. Giraud et al 22 were then able to demonstrate an increase in the nucleation density above that of bare silicon upon using DVA, however coalesced films were not obtained. It is to be noted that in many of the previous studies on the chemical nucleation of diamond growth the diamondoid molecules were spun-coated on substrates by dissolving in solvents like glycol 15 or toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Currently several groups have used different seeding materials ͑without scratching͒ such as graphite fibers, fullerenes clusters, hydrocarbon oil, and thin films of different types of carbon for the diamond deposition. [10][11][12] However, despite rapid progress, the growth of diamond film on the silicon substrate by microwave plasma CVD ͑MPCVD͒ still require nucleation step for improvement in terms of yield, quality, purity, and uniformity to synthesis of diamond at relatively low temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Partial breakdown of adamantane is known to yield carbon clusters ͑C n H x ͒, where n = 3, 5, 6, 7, 8, and 9, of significant abundance. 13 7,10 Another important issue in particular CVD diamond, since early 1980 report is the high deposition temperature ͑700-900°C͒, which limits only on thermal stable substrates. The deposition of high quality diamond at low temperature is still challenging even if some studies reported diamond deposition at temperature below 550°C.…”
Section: Introductionmentioning
confidence: 99%